Cytomegalovirus infection in infants admitted to a neonatal intensive care unit. (July 2013) - Narvaez-Arzate, Ricardo V.; Olguin-Mexquitic, Leticia; Lima-Rogel, Victoria; Noyola, Daniel E.; Barrios-Compean, Lidia M.; Villegas-Alvarez, Carolina
Abstract Objectives: To determine the incidence of congenital cytomegalovirus (CMV) infection and the frequency of postnatal infection in a neonatal intensive care unit (NICU). Methods: Urine samples of 135 infants who were admitted to the NICU during a 6 month period were evaluated to detect CMV using a nested PCR assay. A breast milk sample was obtained to determine viral excretion. Clinical characteristics of infected and non-infected infants were compared. Results: Congenital CMV infection was confirmed in two (1.48%) infants. Post-natal infection was documented in four of 36 (11.1%) infants that were evaluated. CMV excretion was detected in 43 of 116 mothers. Gestational age of infants born to mothers who excreted CMV was shorter than that of infants of mothers with negative results (33.1 versus 34.2 weeks; p = 0.07). Conclusions: CMV excretion in breast milk is frequent and is associated to congenital and postnatal infection. Further studies are necessary to assess the impact of CMV infection during pregnancy and neonatal outcomes.